2014
DOI: 10.1186/1754-9493-8-16
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the WHO Surgical Safety Checklist in an Ethiopian Referral Hospital

Abstract: BackgroundThe WHO Surgical Safety Checklist has a growing evidence base to support its role in improving perioperative safety, although its impact is likely to be directly related to the effectiveness of its implementation. There remains a paucity of documented experience from low-resource settings on Checklist implementation approaches. We report an implementation strategy in a public referral hospital in Addis Ababa, Ethiopia, based on consultation, local leadership, formal introduction, and supported superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
37
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 15 publications
6
37
0
3
Order By: Relevance
“…Fourcade et al reported a checklist completion rate of only 61%, while other studies have reported completion rates as low as 21% [8]- [10]. Levy et al observed compliance rates among 142 pediatric surgical cases over a 7-week period, and reported that none of the cases completed the entire checklist, which was significantly lower than the hospital reported 100% compliance rate [6].…”
Section: Introductionmentioning
confidence: 59%
“…Fourcade et al reported a checklist completion rate of only 61%, while other studies have reported completion rates as low as 21% [8]- [10]. Levy et al observed compliance rates among 142 pediatric surgical cases over a 7-week period, and reported that none of the cases completed the entire checklist, which was significantly lower than the hospital reported 100% compliance rate [6].…”
Section: Introductionmentioning
confidence: 59%
“…There are unique challenges to implementation of the WHO checklist in resource‐limited settings. These include local healthcare infrastructure, access to basic resources, safety culture and sociocultural norms among healthcare workers .…”
Section: Introductionmentioning
confidence: 99%
“…[13] In Pakistan, initial checklist compliance was 20.4%, which increased to 89.9% after 4 years. [14] Bashford et al [15] showed a decline in the compliance rate -from 83% one month after implementation to 18% eight months after implementation.…”
Section: Researchmentioning
confidence: 99%
“…A Pakistani study [14] showed a greater than 4-fold increase in compliance over a 4-year period as training continued and momentum to SSCL use developed. Contradictorily, an Ethiopian study [15] showed a decrease from 83% to 18% in SSCL use over 8 months after implementation, despite ongoing training. In our cohort, 12% of all respondents indicated that inadequate training was a barrier, but 85.9% perceived the need for staff to be trained.…”
Section: Researchmentioning
confidence: 99%